2021
DOI: 10.1017/s1368980021000513
|View full text |Cite
|
Sign up to set email alerts
|

Age difference in the combined effect of soda drinks consumption and body adiposity on hyperuricaemia in US adults

Abstract: Objective: To evaluate age-related differences in the independent/combined association of added sugar intake from soda and body adiposity with hyperuricemia in gender stratified US adults. Design: Consumption of added sugar from soda was calculated from 24-h dietary interviews and categorized into none, regular, and excessive consumption. Hyperuricemia was defined as serum uric acid levels >7 mg/dL in men and >6 mg/dL in women. Multiple regression models with interaction terms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Life-style risk factors, such as excess adiposity, alcohol consumption, cigarette smoking, and sedentary behavior, were found to be associated with hyperuricemia ( 8 , 9 , 11 , 34 38 ). Mendelian randomization studies have demonstrated the causal associations among excess adiposity and alcohol consumption with elevated SUA ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Life-style risk factors, such as excess adiposity, alcohol consumption, cigarette smoking, and sedentary behavior, were found to be associated with hyperuricemia ( 8 , 9 , 11 , 34 38 ). Mendelian randomization studies have demonstrated the causal associations among excess adiposity and alcohol consumption with elevated SUA ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heo and Wylie-Rosett's (2020) research showed a relationship between obesity in high school students and intake of carbonated drinks. Also, Lin et al (2021) (Baxter & Hughes, 2001). Many experts argue that beer is the oldest drink produced by biotechnology processes that have been known since 6000 years in Mesopotamia and the ancient Egyptians knew beer as an intoxicating drink around 3000 years before Christ (Hampson, 2008).…”
Section: Mnemonic Of "Fanta Cola Bir Idamanmentioning
confidence: 99%